Vocal Cord Paralysis after Repair of Esophageal Atresia - Koivusalo, A.I.; Suominen, J.S.; Nokso-Koivisto, J.; Pakarinen, M.P. (European Journal of Pediatric Surgery, 2023)
Objective Etiology of vocal cord paralysis (VCP) and laryngeal dysfunction may be congenital or surgical trauma of recurrent and superior laryngeal nerves. We assessed the incidence, risk factors, and morbidity of VCP after repair of esophageal atresia (EA).Methods Medical records of 201 EA patients from 2000 to 2022 were reviewed for this retrospective study. Postrepair vocal cord examination (VCE) included awake nasolaryngeal fiberoscopy by otolaryngologist or laryngoscopy under spontaneous breathing anesthesia. Before 2017, postoperative VCE was performed in symptomatic patients only and routinely after 2017.Main Results Overall, VCE was performed on 79 (38%) patients (52 asymptomatic), whereas 122 asymptomatic patients underwent no VCE. VCP was diagnosed in 32 of 79 patients (right 12, left 10, and bilateral 10; symptomatic 25 and asymptomatic unilateral 7) corresponding with extrapolated overall VCP incidence of 16 to 24% among 201 patients including asymptomatic ones. Ten patients (bilateral VCP 8 and left VCP 2) required tracheostomy. Of 10 patients with bilateral VCP, three underwent laryngotracheal expansion surgery (left VC lateralization in one and laryngoplasty in two with acquired subglottic stenosis), three remained tracheostomy dependent, three were off tracheostomy, and one died of complications after redo esophageal reconstruction. All patients with unilateral VCP managed without tracheostomy. Cervical dissection or ostomy formation was a major risk factor of VCP.Conclusion Repair of EA is associated with a considerable risk of VCP and associated morbidity. Cervical EA surgery significantly increased the risk of VCP. Bilateral VCP may eventually require laryngotracheal expansion surgery.
Keywords: vocal cord paresis; tracheostomy; esophageal atresia